E-Module Gerak Lurus: Peluang Pengembangan Keterampilan Proses Sains dan Keterampilan Bernalar - Sulur; Munfaridah, Nuril; Agustin, Ela (Universitas Nurul Huda, 2023)
This research aims to develop an e-module based on Predict-Observe-Explain (POE) equipped with questions that refer to the Minimum Competency Assessment (AKM) for high school students on the topic of linear motion that is valid, readable, and practical. This research uses a Research and Development (R&D) research design with a 4D model, namely Define, Design, Develop, and Disseminate. This research produces an e-module for the topic of linear motion in the form of an application that can be used on Android-based devices. E-module has material presented with POE stages in each learning activity, which has the opportunity to improve students' science process skills. Moreover, the e-module is also equipped with AKM questions on the same topic, linear motion, which is expected to improve students' reasoning skills. The results of this research show that the e-module developed is classified as very valid with a percentage of 95.6%. In addition, the e-module also has very good readability and practicality, with a percentage of 94.8%. Thus, the e-module can be used in learning the physics topic, linear motion, for high school students.